First-Line Therapy in Ovarian Cancer Trials. Issue 4 (1st April 2011) - Thigpen, Tate; duBois, Andreas; McAlpine, Jessica; DiSaia, Philip; Fujiwara, Keiichi; Hoskins, William; Kristensen, Gunnar; Mannel, Robert; Markman, Maurie; Pfisterer, Jacobus; Quinn, Michael; Reed, Nick; et al.
Abstract : At the 4th Ovarian Cancer Consensus Conference of the Gynecologic Cancer InterGroup (GCIG) held in Vancouver, Canada, in June 2010, representatives of 23 cooperative research groups studying gynecologic cancers gathered to establish international consensus on issues critical to the conduct of large randomized trials. The process focused on 13 predetermined questions. Group A, 1 of the 3 discussion groups, addressed the first 5 questions, examining first-line therapies in newly diagnosed ovarian cancer patients. A1: What are the appropriate end points for different trials (maintenance, upfront chemotherapy trials including molecular drugs)? A2: Are there any subgroups defined by tumor biology who need specific treatment options/trials? A3: Is the 2004 GCIG-recommended standard comparator arm still valid? A4: What is the role of modifying dose, schedule, and delivery of chemotherapy? A5: What role does surgery play today?